Post-deposition-annealing effect on current conduction in Al2O3 films formed by atomic layer deposition with H2O oxidant - Hiraiwa, Atsushi; Matsumura, Daisuke; Okubo, Satoshi; Kawarada, Hiroshi (Journal of applied physics, 2017)
Atomic-layer-deposition (ALD) Al2O3 films are promising as gate insulators of non-Si semiconductor devices. Although they allow relatively small leakage currents just after deposition, ALD Al2O3 films formed at low temperatures are subject to high temperature during fabrication or operation of devices. Therefore, the effect of post-deposition annealing (PDA) on the properties of Al2O3 films is investigated in this study. ALD Al2O3 films formed using H2O oxidant at low temperatures are compacted by PDA, but their mass density and dielectric constant remain approximately unchanged or slightly decrease owing to the desorption of methyl groups contained in the films as impurities. In accordance with these results, the wet etching rate of Al2O3 films is not much reduced by PDA. The conduction current in ALD Al2O3 films formed on Si is reduced by PDA and becomes smaller than that in films formed at the same ALD temperatures as those of PDA. The conduction current for PDA temperatures above 250 °C, however, increases and, accordingly, spoils the merit of low-temperature ALD. Therefore, given that the dielectric constant of annealed films remains low, high-temperature ALD is practically more significant than applying PDA to low-temperature ALD Al2O3 films from the viewpoint of leakage current under the same thermal budget. Space-charge-controlled field emission analysis revealed that, at the aforementioned threshold temperature, PDA abruptly increases the Al2O3/SiO2 interfacial dipoles and simultaneously reduces the amount of the positive charge near the interface. The so-called negative-charge buildup by PDA might be caused by this decrease in the positive charge.